1963
DOI: 10.1152/ajplegacy.1963.205.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of intestinal fluid loss in irreversible hemorrhagic shock

Abstract: The effect of circulatory hypotension on the small intestine was studied in 42 dogs. The small intestine was clamped at the gastric and ileocecal ends, and the dogs were subjected to control studies or to hypotension of 30 or 40 mm Hg, with and without Dibenzylene, atropine, or vagotomy. The dry gut weight, the wet gut weight, the lumen contents, and the survival time were measured. The increase in gut weight was related entirely to the accumulation of fluid in the lumen of the gut. Vagotomy did not reduce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1967
1967
1985
1985

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Small intestinal fluid and electrolyte transport during hemorrhagic hypotension has been studied by several authors using different experimental animals and methods with varying results. Some investigators have found a increase in fluid and electrolyte absorption after hemorrhage, at least during the early phase (Mailman & Ingraham 1971, Fromm 1973, Mariscotti et al 1977, whereas others, mainly using dogs, have observed a decrease in absorption or a pronounced secretion (Goldberg & Fine 1945, Porciuncula & Crowell 1963, Cook et al 1971.…”
Section: Discussionmentioning
confidence: 99%
“…Small intestinal fluid and electrolyte transport during hemorrhagic hypotension has been studied by several authors using different experimental animals and methods with varying results. Some investigators have found a increase in fluid and electrolyte absorption after hemorrhage, at least during the early phase (Mailman & Ingraham 1971, Fromm 1973, Mariscotti et al 1977, whereas others, mainly using dogs, have observed a decrease in absorption or a pronounced secretion (Goldberg & Fine 1945, Porciuncula & Crowell 1963, Cook et al 1971.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on fluid and electrolyte transport in the small intestine after hemorrhage have revealed either an increase in absorption (Mailman & Ingraham 1971, Fromm 1973, Mariscotti et al 1977 or a decrease which in some studies even turned into a net fluid secretion (Goldberg & Fine 1945, Porciuncula & Crowell 1963, Cook et al 1971. The inconsistent results are probably due to the fact that hemorrhage induces varying changes in blood flow as well as varying nervous and hurnoral changes that directly or indirectly influence intestinal transport capacity.…”
mentioning
confidence: 97%
“…These derangements lead to fluid loss into the interstitium and lumen of the intestine, aggravating the relative hypovolemia due to sequestration [18]. Similar lesions have been reported in human intestinal specimens obtained during or after a period of shock and/or hypotension [10].…”
Section: Discussionmentioning
confidence: 59%